Algorithm Hill Cipher for Securing Arabic Text Documents - Ulin Nihayah; Any Muanalifah; Aini Fitriyah (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2017)
This research is an application of Hill Cipher cryptographic techniques in the process of encoding messages in the form of Arabic text. Hill Cipher is a classic cryptographic algorithm that uses modulo matrix and arithmetic in its application. The Arabic text used in the Hill Cipher cryptographic technique includes hijaiyyah letters ا, ب, , ي, أ, إ, ؤ, ئ, ى, ة, space , ., ،, ؟, !, and Arabic numbers 0, 1, 9, so the modulo used is . This study discusses the steps in encrypting messages with examples of their application in securing Arabic text documents.